Features of the implementation of ESG principles in the corporate governance system of Central Asian countries (Journal of Economic Research & Business Administration, 2025)
The article examines the specific features of implementing ESG principles into the corporate governance systems of Central Asian countries. The relevance of the topic is determined by the need to adapt the national economies of the region to global sustainable development requirements and to increase the transparency of corporate reporting. The aim of the study is to identify institutional differences, barriers, and factors affecting the effectiveness of ESG transformation in the corporate sector of Central Asia.The methodological basis of the study includes systemic, comparative-analytical, and institutional approaches, as well as content analysis of regulatory and legal acts, corporate reports, and statistical data from international organizations for the period 2019-2025.The results showed that Kazakhstan has formed an institutionalized ESG model based on a developed sustainable finance infrastructure, Uzbekistan is implementing a state-centric model, while Kyrgyzstan, Tajikistan, and Turkmenistan are at the stage of institutional formation of the ESG agenda. The key barriers identified include a lack of ESG expertise, a weak regulatory framework, limited financial resources, and low business engagement.The scientific value of the study lies in the development of a comparative model of ESG maturity for the region, while the practical significance lies in formulating directions for improving corporate governance and sustainable financing.Key words: ESG, corporate governance, sustainable development, Central Asia, sustainable finance.